Nutritional status of geriatric patients with mechanical ventilation under intensive care - Jorge Rosales Garcia; Carlos de Dios Perera; Yosbanis Calaña Valdevila; Liyanis Gómez Martínez; Yoan Quesada Castillo (Revista Cubana de Anestesiología y Reanimación, 2019)
Introduction: Malnutrition in patients hospitalized in an intensive care room is high, but it is even higher in the critically-ill elderly patient, with repercussions on the respiratory system, prolonged ventilation, and other complications. Objective: To characterize the nutritional status of geriatric patients under mechanical ventilation in an intensive care unit. Methods: A descriptive, prospective and cross-sectional study was carried out during the period from January 2017 to March 2019, in the intensive care unit of Orlando Pantoja Tamayo General Teaching Hospital. 83 patients aged 60 or older were studied; they required mechanical ventilation for more than 24 hours. The nutritional status was evaluated with the use of the nutritional control score. Results: There was a predominance of the male sex, the age group 60-74 years, and of surgical diseases. Only 9.1% of those who received invasive mechanical ventilation were not undernourished. Those who died had moderate or severe undernutrition. Conclusions: In ventilated geriatric patients hospitalized in the intensive care unit, a high degree of malnutrition was found. Moderate or severe malnutrition predominated in the majority of those who received invasive mechanical ventilation and in the group of the deceased.  Keywords:   critically-ill patient; control; mechanic ventilation; nutritional status.